English Teachers’ Perceptions of The Role of Visual Literacy in Students’ Reading Comprehension: (A Case Study at SMA N 2 Batang in the Academic Year of 2024/2025) - Fitriana, Dhesta; Permanasari, Pradnya (Pusdikra-Publishing.com, 2025)
This study investigates how English teachers perceive the role of visual literacy in students' reading comprehension at SMA Negeri 2 Batang. The background of this study stems from the challenges faced by students in understanding complex English texts and the limited use of visual media in teaching by teachers. The purpose of this study is to determine how teachers apply visual literacy in teaching, as well as to understand their views on the benefits and challenges faced. Using a qualitative approach and case study method, data was collected through observation, in-depth interviews, and documentation. The results of the study indicate that visual literacy, such as images, videos, and infographics, can significantly improve students' comprehension and motivation to learn. The teachers stated that the use of visual media helps students connect text with context, enriches learning experiences, and fosters reading interest. However, its implementation still faces several challenges, such as time constraints, facilities, and teachers' skills in selecting and integrating visual media effectively into teaching materials. Therefore, appropriate training for teachers and balanced learning strategy planning are needed so that visual literacy can be used not merely as an addition but as an integral part of the reading-learning process. With proper management, the integration of visual literacy can strengthen students' overall English literacy skills.